Qualitative experiences of disengagement in assertive outreach teams, in particular for "black" men: Clinicians' perspectives. Issue 2 (27th November 2017) - Wagstaff, C.; Graham, H.; Salkeld, R.
Accessible summary: This study is a follow‐on study to a study into the experiences of disengagement from mental health services for men who described their ethnic identity as "black." The aim of this study was to understand the same phenomenon from a clinician's perspective. What is known on the subject?: Literature highlights that people from ethnic minority backgrounds experience some difficulties engaging with mental health services; Disengagement from mental health services is a complex phenomenon that occurs for a variety of different reasons; Only one paper previously has investigated clinicians' perspective on disengagement from mental health services; What the study adds to existing knowledge?: This study demonstrates that clinicians are aware that stigma and medication impact upon engagement with mental health services, which were also important components of the patients experience. A finding of the former study was that patients' attitudes towards mental health services change over time, with patients engaging more as they get older, a finding was supported by wider literature. However, in this study, the participants were not certain that this was the case. What are the implications for practice?: The implications for practice from this study are that staff should persist with efforts to reduce the stigma surrounding mental health, carefully consider the significance and impact of medication and have an awareness of how patients' attitudes towards mental illness and mental health services change and develop over time. Continued support for an AO approach to practice for people who find it difficult to engage with services, where a multidisciplinary "team" approach can focus on service user‐centred recovery goals and a positive space for collaboration. Abstract: Introduction: Engagement with services is often poor amongst people with severe mental health problems, yet key to improving clinical outcomes. Aims: This study explores the perception of clinicians on patients with severe mental health problems, in particular the experiences of black men, who disengage from mental health services. Method: Two focus groups consisting of a combined total of twelve, mainly white, experienced clinicians in the UK were recruited. Transcripts were analysed using interpretative phenomenological analysis. Results: Clinicians understood that patients' awareness of stigma impacted upon engagement with mental health services. Clinicians were aware that medication negatively impacted on engagement. The passage of time was perceived as impacting upon engagement. Discussion: The perspectives of the clinicians in this study and the experiences of the patients in a former study converged. The participants had an understanding of the complexities that black men faced when engaging with mental health services. Implications for practice: This is the first study to highlight that AOT staff need to be aware of the key role that stigma plays in engagement in treatment, continue to focus on efforts to reduce the stigma surrounding mental health, consider the significance medication and be aware of how patients' attitudes towards mental health services develop over time.